Effect of multiwall carbon nanotube loading on multi filler polymer composite as bipolar plate - Bairan, Aninorbaniyah (UTeM, 2018)
Apart from achieving homogeneous Multiwall Carbon Nanotube (MWCNTs) dispersion in nanocomposites and preventing agglomeration of MWCNTs due to Van der Waals attraction forces, the main challenge here is to enhance the interfacial compatibility between MWCNTs and nonpolar polypropylene (PP). Therefore, the aim of this study was to identify the most effective and suitable ratio of MWCNTs loading through two mixing methods. The ratio of fillers and binder was fixed at 80:20, while the conductive fillers of MWCNTs (0% up to 10%), G (45% up to 55%) and CB was set to 25% of the weight percentage of G/CB/MWCNTs/PP composite. The multi filler of Graphite (G), Carbon Black (CB) and MWCNTs composite using a medium density polypropylene (MDPP) as binder was mixed through melt compounding method. The second mixing method is through dry mixing method by using MDPP and low density polypropylene (LDPP) as binders. The composite were fabricated through compression molding. The results included the characterization of electrical and mechanical properties and analysis of the hydrogen gas permeability and surface morphology of the composites. The effective MWCNTs loading is in the range of 5 wt.% up to 7 wt.% of MWCNTs and based on the two methods, melt compounding method is better than dry mixing method in terms of its electrical conductivity and mechanical properties. For melt compounding method, it was found that using MWCNTs as a third filler at a loading of 5 wt.% in a G/CB/MDPP composite produced higher results of in-plane electrical conductivity; 518.90 S/cm, the flexural strength, density and shore hardness 61.43 MPa, 1.61 g/cm3 and 65.1 (SH) respectively. Meanwhile, through dry mixing method for the MWCNTs/MDPP composite, the electrical conductivity is 158.32 S/cm with 6 wt.% MWCNTs content. The flexural strength of MWCNTs/MDPP increased from 22.95 MPa (3 wt.%) to 29.86 MPa (5 wt.%) with the increment of MWCNTs content. Results also indicated that there was no leaking gas occurred during the permeability test at 5 wt.% MWCNTs content for melt compounding and dry mixing (LDPP) and 6 wt. % MWCNTs for dry mixing (MDPP). These results confirm that melt compounding methods and the addition of MWCNTs lead to a significant improvement on the properties of the conducting polymer composite as bipolar plate.